Konsep Mukmin dalam Tafsir Al-Qur'an Bi Al-Imla’ Karya KH. Zaini Mun’im - A. Rafiq Zainul Mun'im (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2013)
As a descriptive exploration, this article presents the view of KH. Zaini Mun’im with regards to the term Muslim (mukmin) in chapter al-Baqarah verses 1-5 in Tafsir al-Qur'an bi al-Imla. This study serves as an appreciation of the Nusantara intellectual manuscript, an unprinted resource yet obviously valuable and worthy of further research. The result of this investigation shows that the term Muslim refers to a man (human being) who has obtained guidance and thereby follows the Quran’s command. This individual has implemented the concept of fundamental beliefs and creeds into his social live. The creeds comprises believe in the invisible, performs obligatory prayers, sharing God’s blessing, believe in the books of God revealed to His Prophets, and believe in eschatology.